2007
DOI: 10.1111/j.1750-3841.2007.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ortho‐ and Retronasal Detection Thresholds for 2‐Isopropyl‐3‐Methoxypyrazine in Wine

Abstract: 2-Isopropyl-3-methoxypyrazine (IPMP) is a grape-derived component of wine flavor in some wine varieties as well as the causal compound of the off-flavor known as ladybug taint (LBT), which occurs when Harmonia axyridis beetles are incorporated with the grapes during juice and wine processing. The main objective of this study was to obtain robust estimates of the orthonasal (ON) and retronasal (RN) detection thresholds (DTs) for IPMP in wines of differing styles. The ASTM E679 ascending forced choice method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 26 publications
5
48
2
Order By: Relevance
“…Pickering et al (2007) exploring sensitivity of 2-isopropyl-3-methoxypyrazine in wine showed that winemakers have lower detection threshold than non-winemakers. They explained this result by a familiarization with the related wine defect was thus invoked rather than a gain in olfactory acuity.…”
Section: Inter-individual Variations Of Intrinsic Sensitivitymentioning
confidence: 99%
“…Pickering et al (2007) exploring sensitivity of 2-isopropyl-3-methoxypyrazine in wine showed that winemakers have lower detection threshold than non-winemakers. They explained this result by a familiarization with the related wine defect was thus invoked rather than a gain in olfactory acuity.…”
Section: Inter-individual Variations Of Intrinsic Sensitivitymentioning
confidence: 99%
“…3-Alkyl-2-methoxypyrazines (MPs) are powerful, odourous components of many wines, where thresholds have been reported as low as 320 pg/L (Pickering, Karthik, Inglis, Sears, & Ker, 2007). 3-Isopropyl-2-methoxypyrazine (IPMP), 3-s-butyl-2-methoxypyrazine (SBMP) and 3-isobutyl-2-methoxypyrazine (IBMP) are secondary plant metabolites that are most abundant in grape Vitis vinifera varieties that originate from the Bordeaux region in France, especially Cabernet Sauvignon (Allen, Lacey, & Boyd, 1994;Kotseridis, Baumes, Bertrand, & Skouromounis, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The first judgement procedure is commonly used in experiments that involve simultaneous testing on multiple judges (Kolpin & Shellhammer, 2009;Pickering, Karthik, Inglis, Sears, & Ker, 2007;Plotto, Margaria, Goodner, Goodrich, & Baldwin, 2004;Stocking, Suffet, McGuire, & Kavanaugh, 2001). A full evaluation of all 3AFC trials is collected from each judge, and the threshold is estimated from the location in the series at which the response reversed from incorrect to correct for the last time.…”
Section: Introductionmentioning
confidence: 99%